2018
DOI: 10.1016/j.vaccine.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro immunogenicity of novel MHC class I presented epitopes to confer protective immunity against chronic HTLV-1 infection

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) has infected approximately 20 million people worldwide. While 90% are asymptomatic, 5% develop severe diseases including adult T-cell leukemia/lymphoka (ATLL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). No vaccine against HTLV-1 exists, and screening programs are not universal. However, patients with chronic HTLV-1 infection have high frequencies of HTLV-1-activated CD8+ T cells, and the two main HLA alleles (A2, A24) are present in 88% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…6 B). Granzyme B, MIP-1α, IFN-γ, and TNF-α are part of the innate immune response and are mainly produced by NK and natural killer T (NKT) cells [ 22, 23 ]. Interestingly, it was shown that PDIA6 knockdown alone had no significant effect on Granzyme B, MIP-1α, IFN-γ, and TNF-α levels in PC cells.…”
Section: Resultsmentioning
confidence: 99%
“…6 B). Granzyme B, MIP-1α, IFN-γ, and TNF-α are part of the innate immune response and are mainly produced by NK and natural killer T (NKT) cells [ 22, 23 ]. Interestingly, it was shown that PDIA6 knockdown alone had no significant effect on Granzyme B, MIP-1α, IFN-γ, and TNF-α levels in PC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although an HTLV-1 preventative vaccine is feasible, no candidate vaccine has ever proceeded to clinical trial. Vaccine development efforts have used recombinant vaccinia virus vectors, protein immunization, DNA vaccine vectors, and peptide vaccines [ 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ]. Collectively, these data suggest that an immune-based intervention based on vaccination alone is unlikely to be effective in the context of chronic HTLV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…MHC-I-bound HTLV-1 peptides have been identified which give rise to HTLV-1-specific CTLs in vivo ( 79 ). A therapeutic vaccine to activate TAX-specific CTLs was developed using TAX peptide-pulsed dendritic cells, resulting in favorable clinical outcomes in three ATLL patients ( 80 , 81 ).…”
Section: Vaccination Against Htlv-1mentioning
confidence: 99%